2015
DOI: 10.1002/pd.4655
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and reproducibility of ShearWaveTM elastography of fetal baboon organs

Abstract: Transabdominal ShearWave(TM) Elastography of fetal organs can be achieved in pregnant baboons. The intra-observer and inter-observer reproducibility is correct but vary according to the targeted organs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…These methods generate a considerably higher thermal index (TI) than a conventional US examination does. For that reason, some authors have studied SWE™ on animals (pregnant baboons) rather than pregnant women [ 23 , 42 ]. Although the early data appear reassuring, it is currently too early to generalize the use of these techniques on pregnant women and their fetuses.…”
Section: Introductionmentioning
confidence: 99%
“…These methods generate a considerably higher thermal index (TI) than a conventional US examination does. For that reason, some authors have studied SWE™ on animals (pregnant baboons) rather than pregnant women [ 23 , 42 ]. Although the early data appear reassuring, it is currently too early to generalize the use of these techniques on pregnant women and their fetuses.…”
Section: Introductionmentioning
confidence: 99%
“…Data on intrauterine elastographic evaluation of foetal tissues are very limited, with a few studies available in the literature using baboon foetuses as an experimental model (Quarello, Lacoste, Mancini, Melot‐Dusseau, & Gorincour, ,b; Quarello et al., ) and a single study evaluating human foetuses (Zheng, Wu, & Tan, ). These studies demonstrated the feasibility, reproducibility and applicability of elastography in the evaluation of maternal and foetal tissues, revealed important information about normal elasticity standards, however, have shown only weak correlation between elastography variables and gestational development.…”
Section: Introductionmentioning
confidence: 99%
“…It is, however, important to acknowledge that the present results could have been affected by peristaltic movements occurring in pregnant bitches, variability in foetal organ depth, foetal movements, acoustic shadowing generated by foetal ribs, and the proportions of areas of interest evaluated. These limitations of both imaging techniques have previously been described by Quarello et al (2015) and may impinge on the detection of relationships between echotextural and elastographic characteristics of foetal lungs and livers.…”
Section: Discussionmentioning
confidence: 99%